ENHANCEMENT OF THE CALORIFIC VALUE OF EM1707PTY FRUIT BUNCH (EFB) BY ADDING MUNICIPAL SOLID WASTE AS SOLID FUEL IN GASIFICATION PROCESS - Diallo, Amadou Dioulde Donghol; Alkhatib, Ma’an Fahmi Rashid; Alam, Md Zahangir; Mel, Maizirwan (IIUM Engineering Journal, 2021)
Empty fruit bunch (EFB), a biomass-based waste, was deemed a potential replacement for fossil fuel. It is renewable and carbon neutral. The efficient management of this potential energy will help to deal with the problem associated with fossil fuels. However, a key parameter for evaluating the quality of raw material (EFB) as a fuel in energy applications is the calorific value (CV). When this CV is low, then its potential utilization as feedstock will be restricted. To tackle this shortcoming, we propose to add municipal solid waste to enhance energetic value. Thus, two major issues will be solved: managing solid residues and contributing an alternative energy source. This study aimed to investigate the possibility of mixing EFB and municipal solid waste (MSW) to make clean energy that is conscious of the environment (climate change) and sustainable development. The selected MSW, comprising of plastics, textiles, foam, and cardboard, were mixed, with EFB at various ratios. Proximate analysis was used to determine moisture content, ash, volatiles, and fixed carbon, whilst elemental analysis, is used to determine CHNS/O for MSW, EFB and their various mixtures. The CV of each element was also measured. The research revealed a significant increase in the calorific value of EFB by mixing it with MSW according to MSW/EFB ratios: 0.25; 0.42; 0.66; 1.00 and 1.50 the corresponding calorific values in (MJ/kg) were 19.77; 21.22; 22.67; 27.04 and 28.47 respectively. While the calorific value of pure EFB was 16.86 MJ/kg, the mixing of EFB with MSW promoted the increase in the CV of EFB to an average of 23.83MJ/kg. Another potential environmental benefit of applying this likely fuel was the low chlorine (0.21 wt. % to 0.95 wt. %) and sulfur concentrations (0.041 wt. % to 0.078 wt.%). This potential fuel could be used as solid refuse fuel (SRF) or refuse-derived fuel (RDF) in a pyrolysis or gasification process with little to no environmental effects. ABSTRAK: Tandan buah kosong (EFB), sisa berasaskan biojisim, adalah berpotensi sebagai pengganti bahan bakar fosil. Ia boleh diperbaharui dan karbon neutral. Pengurusan berkesan pada potensi tenaga ini dapat membantu mengatasi masalah melibatkan bahan bakar fosil. Namun, kunci parameter bagi menilai kualiti bahan mentah (EFB) sebagai bahan bakar dalam aplikasi tenaga adalah nilai kalori (CV). Apabila CV rendah, potensi menjadi stok suapan adalah terhad. Sebagai penyelesaian, kajian ini mencadangkan sisa pepejal bandaran ditambah bagi meningkatkan nilai tenaga. Oleh itu, dua isu besar dapat diselesaikan: mengurus sisa pepejal dan menambah sumber tenaga alternatif. Kajian ini bertujuan mengkaji potensi campuran tandan buah kosong (EFB) dan sisa pepejal bandaran (MSW) bagi menghasilkan tenaga bersih dari sudut persekitaran (perubahan iklim) dan pembangunan lestari. Pemilihan MSW, terdiri daripada plastik, tekstil, gabus dan kadbod, dicampurlan dengan pelbagai nisbah EFB. Analisis proksimat telah digunakan bagi mendapatkan kandungan kelembapan, abu, ruapan, dan karbon tetap, manakala analisis asas telah digunakan bagi mendapatkan CHNS/O bersama MSW, EFB dan pelbagai campuran lain. Nilai kalori (CV) setiap elemen turut diukur. Dapatan kajian menunjukkan penambahan ketara dalam nilai kalori EFB dengan campuran bersama MSW berdasarkan nisbah MSW/EFB 0.25; 0.42; 0.66; 1.00 dan 1.50 nilai kalori sepadan (MJ/kg) adalah 19.77; 21.22; 22.67; 27.04 dan 28.47 masing-masing. Manakala nilai kalori EFB tulen adalah 16.86 MJ/kg, campuran EFB dan MSW menunjukkan kenaikan CV dengan EFB pada purata 23.83MJ/kg. Antara potensi semula jadi lain adalah dengan mencampurkan bahan bakar ini dengan kalori rendah (0.21 wt. % kepada 0.95 wt. %) dan kepekatan sulfur (0.041 wt. % kepada 0.078 wt.%). Bahan bakar ini berpotensi sebagai bahan bakar pepejal sampah (SRF) atau bahan bakar yang terhasil dari pepejal sampah (RDF) melalui proses pirolisis atau proses gasifikasi yang sedikit atau tiada kesan langsung terhadap persekitaran.